Residential traffic and incidence of Type 2 diabetes: the German Health Interview and Examination Surveys. Issue 10 (30th May 2014) - Heidemann, C.; Niemann, H.; Paprott, R.; Du, Y.; Rathmann, W.; Scheidt‐Nave, C.
Abstract Aims To investigate whether an indicator of overall traffic intensity is related to the risk of Type 2 diabetes in a nationwide cohort. Methods The study population comprised 3604 adults aged 18–79 years and without diabetes from the German National Health Interview and Examination Survey (GNHIES98, 1997–1999) who participated again in a follow‐up survey (DEGS1, 2008–2011). The association between the participants' reported traffic intensity at their residential address and Type 2 diabetes incidence was examined using logistic regression models. Results During a mean of 12.1 years of follow‐up, 252 of the participants included in the study developed Type 2 diabetes. Compared with people living in traffic‐calmed areas, odds ratios were 1.15 (95% CI 0.80–1.67) for people living on moderately busy side streets, 1.11 (95% CI 0.69–1.80) for people living on considerably busy side streets, 1.41 (95% CI 0.96–2.08) for people living on heavily busy roads, and 1.97 (95% CI 1.07–3.64) for people living on extremely busy roads, after adjusting for age, sex, active and passive smoking, type of heating, education, BMI, waist circumference, sport activity and parental diabetes history. Conclusions The twofold higher risk of Type 2 diabetes observed for people exposed to intense traffic in this nationwide cohort extends the limited evidence from previous selected populations. Although the underlying traffic‐related components and their biological mechanisms still need to be unravelled, traffic exposure control should be considered in public health strategies to reduce the global burden of diabetes.